Digital storytelling and teacher education: an experience in initial teacher training - Marco Lazzari (Firenze University Press, 2016)
A group of pre-service teachers experienced the digital storytelling as part of their e-learning duties. We describe the structure of the project-work carried out by the students and discuss the results of a questionnaire they filled out after the end of the course, aiming to gather their opinions. The students claim to have enjoyed the proposal and most of them are likely to repeat it in their school, either by developing digital stories themselves or by involving their future students as designers and developers. By questionnaire and interviews with the participants, it is clear that the development experience has changed their attitude towards educational technology, enhanced their digital skills, and increased their self-esteem. Digital storytelling nella formazione iniziale degli insegnanti: un'esperienza nel Tirocinio Formativo Attivo Un gruppo di aspiranti insegnanti iscritti al Tirocinio Formativo Attivo ha affrontato un'esperienza di digital storytelling come parte dei compiti di didattica a distanza. Viene qui descritta la struttura del lavoro svolto dai corsisti e si riflette sui risultati di un questionario sottoposto al termine del corso per rilevarne le opinioni. I corsisti dichiarano di aver gradito la proposta e buona parte di loro ritiene probabile ripeterla a scuola, anche coinvolgendo gli studenti nel progetto e nella realizzazione di narrazioni digitali multimediali. Da questionario e colloqui con i corsisti si deduce che l'esperienza di sviluppo ha mutato il loro atteggiamento verso le tecnologie didattiche, aumentato la loro efficacia come comunicatori digitali e accresciuto la loro autostima.